Wherever He Goes: An Ars Moriendi for Perinatal Hospice - Courtois, Mariele (Christian bioethics, 2025)
Advancements in prenatal testing and genetic screening continually improve the detection of life-limiting conditions that have no treatment or cure. Thus, more parents face the heartbreaking news that their child may die shortly after birth. In response to problems with medicalized dying, Cicely Saunders started the hospice movement in the 1950s. Perinatal hospice, which brings hospice and palliative care into neonatology, can meet some of the needs of families whose children receive life-limiting diagnoses, but this essay describes how perinatal hospice might be further improved by integrating insights from the late medieval Christian ars moriendi tradition. The dying infant requires a particularly family-based ars moriendi. The article proposes recommendations for medical practitioners to improve perinatal hospice. These recommendations would help families contemplate death, celebrate the child’s birthday, prepare for accompaniment, and preserve memories. This ars moriendi illuminates an art of perinatal hospice to benefit the child, family, and clinicians.